2006
DOI: 10.1364/ao.45.003688
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mueller polarimetry in conical diffraction for critical dimension measurements in microelectronics

Abstract: Fast and efficient metrology tools are required in microelectronics for control of ever-decreasing feature sizes. Optical techniques such as spectroscopic ellipsometry (SE) and normal incidence reflectometry are widely used for this task. In this work we investigate the potential of spectral Mueller polarimetry in conical diffraction for the characterization of 1D gratings, with particular emphasis on small critical dimensions (CDs). Mueller matrix spectra were taken in the visible (450-700 nm) wavelength rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 15 publications
0
57
0
Order By: Relevance
“…8 A recent study on spectroscopic MMP reported that the Mueller matrices obtained in some measurement configurations may help decorrelate the fitting structural parameters. 9 They further proposed to choose the measurement configuration with small parameter correlations and small estimated precision of the structural parameters. 10 It is also interesting to note from the previous works 4,5,10 that the accuracy of the extracted structural parameters varies greatly in different measurement configurations.…”
Section: Introductionmentioning
confidence: 99%
“…8 A recent study on spectroscopic MMP reported that the Mueller matrices obtained in some measurement configurations may help decorrelate the fitting structural parameters. 9 They further proposed to choose the measurement configuration with small parameter correlations and small estimated precision of the structural parameters. 10 It is also interesting to note from the previous works 4,5,10 that the accuracy of the extracted structural parameters varies greatly in different measurement configurations.…”
Section: Introductionmentioning
confidence: 99%
“…2 Optical critical dimension (OCD) analysis makes use of this data in conjunction with a structure that closely matches the experimental reality (using SEM, TEM, and so on, information) to model the system. 3 Typically, some regression-based fitting is involved, i.e., structural parameters are varied in order to minimize deviation from the experimental data. 4 When the figure-of-merit (usually mean square error) is minimized, the structural parameters are determined and compared again to other metrology tools for value confirmation, although some variation is expected depending on the method used for comparison.…”
Section: Ellipsometry and Optical Critical Dimensionmentioning
confidence: 99%
“…However, Mueller measurements have better sensitivities to small structural changes and provide more information about the sample than traditional spectroscopic ellipsometry (SE) and spectroscopic reflectometry (SR) measurement. 9,10 Profile reconstruction of patterned structures in scatterometry models that incorporate line roughness has been largely neglected likely because it increases the number of floating parameters and the correlation between these parameters and computation time. The multiparameter scatterometry models that include the surface roughness as demonstrated in this study can be used offline for predictive modeling and a librarybased search can be carried out as a quick and effective approach for LER measurements.…”
Section: Introductionmentioning
confidence: 99%